Activation mechanisms of the Hippo kinase signaling cascade - Bae, Sung Jun (Biosci Rep, 2018)
First discovered two decades ago through genetic screens in Drosophila, the Hippo pathway has been shown to be conserved in metazoans and controls organ size and tissue homeostasis through regulating the balance between cell proliferation and apoptosis. Dysregulation of the Hippo pathway leads to aberrant tissue growth and tumorigenesis. Extensive studies in Drosophila and mammals have identified the core components of Hippo signaling, which form a central kinase cascade to ultimately control gene expression. Here, we review recent structural, biochemical, and cellular studies that have revealed intricate phosphorylation-dependent mechanisms in regulating the formation and activation of the core kinase complex in the Hippo pathway. These studies have established the dimerization-mediated activation of the Hippo kinase (mammalian Ste20-like 1 and 2 (MST1/2) in mammals), the dynamic scaffolding and allosteric roles of adaptor proteins in downstream kinase activation, and the importance of multisite linker autophosphorylation by Hippo and MST1/2 in fine-tuning the signaling strength and robustness of the Hippo pathway. We highlight the gaps in our knowledge in this field that will require further mechanistic studies.